Developments in the formulation and reinforcement of concrete - Mindess, Sidney (Woodhead Publishing in materials, 2008)
Concrete is the most widely-used construction material in the world. This important book summarises the wealth of recent research on improving qualities such as durability and sustainability as well as the emergence of a new generation of specialist concretes for particular applications.